Comparison of the outcomes after haploidentical and cord blood salvage transplantations for graft failure following allogeneic hematopoietic stem cell transplantation - Harada, Kaito; Fuji, Shigeo; Seo, Sachiko; Kanda, Junya; Ueki, Toshimitsu; Kimura, Fumihiko; Kato, Koji; Uchida, Naoyuki; Ikegame, Kazuhiro; Onizuka, Makoto; Matsuoka, Ken-ichi; Doki, Noriko; et al. (Bone marrow transplantation (Basingstoke), 2020)
Graft failure (GF) is a life-threatening complication after allogeneic stem cell transplantation (SCT). Although salvage SCTs can be performed with haploidentical donor (HID) or cord blood (CB), no study has compared the performances of these two sources. Using nationwide registration data, we compared the transplant outcomes of patients who developed GF and underwent salvage transplantation from HID ( n = 129) and CB ( n = 570) from 2007 to 2016. The HID group demonstrated better neutrophil recovery (79.7 vs. 52.5% at 30 days, P < 0.001). With a median follow-up of 3 years, both groups demonstrated similar overall survival (OS) and nonrelapse mortality (NRM; 1-year OS, 33.1 vs. 34.6% and 1-year NRM, 45.1 vs. 49.8% for the HID and CB groups). After adjustments for other covariates, OS did not differ in both groups. However, HID was associated with a lower NRM (hazard ratio, 0.71; P = 0.038) than CB. The incidence of acute graft-versus-host disease (GVHD)-related deaths was significantly higher in the HID group, although infection-related deaths were observed more frequently in the CB group. HID may be a promising salvage SCT option after GF due to its faster engraftment and low NRM.